The Role of C-Reactive Protein in Kidney, Bladder, and Prostate Cancers - O’Brian, Daniel; Prunty, Megan; Hill, Alexander; Shoag, Jonathan (Frontiers in Immunology, 2021)
C-Reactive Protein (CRP) has been shown to be associated diverse outcomes in patients with, or suspected to have, genitourinary malignancies. CRP levels have been shown to be associated with the probability of a prostate cancer diagnosis in patients with elevated PSA, the probability of biochemical recurrence following definitive treatment for localized prostate cancer, and decreased overall survival for patients with advanced disease. In patients with bladder and kidney cancers, CRP levels have been associated with disease progression, stage, and cancer-specific survival. Despite the abundance of correlative studies, the relationship between CRP levels and genitourinary cancer pathogenesis is not clearly understood. Here, we review the evidence for CRP as a biomarker in genitourinary (GU) cancers, with specific focus on potential clinical applications.